2020
DOI: 10.1039/c9ee03027a
|View full text |Cite
|
Sign up to set email alerts
|

High-purity pyrrole-type FeN4 sites as a superior oxygen reduction electrocatalyst

Abstract: High-purity pyrrole-type FeN4 sites have been developed as a superior oxygen reduction catalyst for proton exchange membrane fuel cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
271
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 373 publications
(299 citation statements)
references
References 42 publications
15
271
0
Order By: Relevance
“…[ 14 ] Among the various MN 4 coordination catalysts, FeN 4 is reported to exhibit the highest ORR activity, whose intrinsic activity is reported as high as 6.89 mA m −2 . [ 15a ] The current explanation of the promising ORR activity on FeN 4 mainly focus on the viewpoint of electronic structures or free energy diagram computed through DFT calculations. For example, Wu and co‐workers have computed the density of states (DOS) of FeN 4 with and without a 2% FeN bond contraction ( Figure a) and attributed the better activity of FeN 4 with FeN bond contraction to the positive shifting of the 3d orbitals of central Fe, which facilitates oxygen adsorption on FeN 4 sites (Figure 3b).…”
Section: Examples Of Spin‐electrocatalysis In Oer and Orrmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 14 ] Among the various MN 4 coordination catalysts, FeN 4 is reported to exhibit the highest ORR activity, whose intrinsic activity is reported as high as 6.89 mA m −2 . [ 15a ] The current explanation of the promising ORR activity on FeN 4 mainly focus on the viewpoint of electronic structures or free energy diagram computed through DFT calculations. For example, Wu and co‐workers have computed the density of states (DOS) of FeN 4 with and without a 2% FeN bond contraction ( Figure a) and attributed the better activity of FeN 4 with FeN bond contraction to the positive shifting of the 3d orbitals of central Fe, which facilitates oxygen adsorption on FeN 4 sites (Figure 3b).…”
Section: Examples Of Spin‐electrocatalysis In Oer and Orrmentioning
confidence: 99%
“…For example, Wu and co‐workers have computed the density of states (DOS) of FeN 4 with and without a 2% FeN bond contraction ( Figure a) and attributed the better activity of FeN 4 with FeN bond contraction to the positive shifting of the 3d orbitals of central Fe, which facilitates oxygen adsorption on FeN 4 sites (Figure 3b). [ 15b ] Xie and co‐workers calculated the free energy diagrams of ORR on pyrrole‐type and pyridine‐type FeN 4 . They found that pyrrole‐type FeN 4 exhibits lower thermodynamic overpotential (0.35 eV) from the initial state (O 2 ) to the final state (H 2 O) than that of pyridine‐type (0.67 eV) in a typical 4e − pathway.…”
Section: Examples Of Spin‐electrocatalysis In Oer and Orrmentioning
confidence: 99%
“…As shown in Figure 5(c), Fe-N-C catalysts were reported from Fe-dual pyridine coordination complexes, which exhibit highly efficient oxygen reduction [132]. Our group [133] revealed that, compared to pyridinic and graphitic N, a high-purity pyrrole-type FeN 4 electrocatalysts regulated the atomic and electronic structure of active sites ( Figure 5(d)), which greatly enhanced high intrinsic catalytic activity. Based on the X-ray absorption near edge structure (XANES) analysis and fitting results, the detailed arrangement of carbon in Fe-N x -C moieties was revealed as FeN 4 C 12 .…”
Section: Atomic Coordination Configurationmentioning
confidence: 84%
“…[57] Highpurity pyrrole-type Fe-N 4 motifs were achieved via topochemical transformation from pyridinic N to pyrrolic N, with the assistance of the NH 3 -etching approach (Figure 3c). [58] The N-K edge X-ray absorption near edge structure (XANES) spectra indicate the presence of Fe-pyrrolic N coordination structure without pyridinic-N coordinated Fe sites in as-prepared catalysts. The pyrrole-type FeN 4 sites are preferable for oxygen adsorption and exhibit a better kinetic activity for ORR than these of other references in acidic electrolytes (Figure 3d), as supported by experimental and DFT results.…”
Section: Heteroatom Dopingmentioning
confidence: 99%
“…c,d) Reproduced with permission. [58] Copyright 2020, Royal Society of Chemistry. e) Reproduced with permission.…”
Section: Heteroatom Dopingmentioning
confidence: 99%